Mating calls description of five species of frogs from the genus Hylarana Tschudi 1838 ( Amphibia, Anura, Ranidae) from Sarawak, Malaysia. - Ramlah, Zainudin; Mustafa, Abdul Rahman; Badrul Munir, Md Zain; M.N, Shukor; R.F., Inger; Norhayati, Ahmad (Universiti Kebangsaan Malaysia (UKM), 2010)
Recordings of frog calls from the genus Hylarana were conducted at seven study sites in Sarawak, Malaysia. The results showed that each species differs in terms of call characteristics, in which a high number of pulsed note belongs to H. baramica, while high repetition note belongs to the sibling species, H. glandulosa. Higher pitched and number of amplitude spectrum, however, belong to H. signata. Pulsed note and note repetition differed significantly among species, except for spectrum amplitude. Advertisement calls for each species were described in detail. This study provide a baseline data on advertisement call characteristics of frogs from the genus Hylarana for future studies of these frogs particularly and the Oriental frogs generally.